Free Light Chains and Intrathecal B Cells Activity in Multiple Sclerosis: A Prospective Study and Meta-Analysis. (28th December 2016) - Passerini, Gabriella; Dalla Costa, Gloria; Sangalli, Francesca; Moiola, Lucia; Colombo, Bruno; Locatelli, Massimo; Comi, Giancarlo; Furlan, Roberto; Martinelli, Vittorio
Abstract : Background . The presence of CSF oligoclonal bands (OBs) is an independent prognostic factor for multiple sclerosis (MS), but the difficulties in the standardization of the test and the interlaboratory variation in reporting have contributed to its limited use in the diagnosis of the disease. Standard nephelometric assays to measure free light chains (FLC) levels have been recently developed and the test may improve the detection of intrathecal B cells activity. Methods . The presence of OBs, kappa and lambda FLC levels, and standard indices of intrathecal inflammation were assessed in 100 consecutive patients, including patients with MS, clinically isolated syndromes (CIS), other inflammatory diseases of the CNS, and other noninflammatory diseases. Results . Both KFLC and LFLC correlated strongly with the presence of OCBs and with all common tests for intrathecal inflammation (p < 0.001 for all comparisons). KFLC and LFLC were significantly different in patients with MS and CIS compared to the other groups (p < 0.001 andp < 0.001, resp.) and had a better diagnostic accuracy than all the other tests (area under the curve 82.3 % for KFLC index and 79.3 % for LFLC index). Conclusion . Nephelometric assays for KFLC in CSF reliably detect intrathecal immunoglobulin synthesis and discriminate MS patients.